2007
DOI: 10.1111/j.1399-3054.2007.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate warming and species richness on photochemistry of grasslands

Abstract: In view of the projected climatic changes and the global decrease in plant species diversity, it is critical to understand the effects of elevated air temperature (T(air)) and species richness (S) on physiological processes in plant communities. Therefore, an experiment of artificially assembled grassland ecosystems, with different S (one, three or nine species), growing in sunlit climate-controlled chambers at ambient T(air) and ambient T(air) + 3 degrees C was established. We investigated whether grassland s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
1
14
2
Order By: Relevance
“…Previous long‐term studies conducted on grassland populations did not find any indications of PSII acclimatization after long‐term exposure to unfavorable conditions. Gielen et al (), who exposed grassland populations to high temperatures over 3 years, did not observe improved PSII tolerance to midday stress compared with the control. In contrast, the midday depression of F V /F M was stronger for populations grown under high air temperature conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Previous long‐term studies conducted on grassland populations did not find any indications of PSII acclimatization after long‐term exposure to unfavorable conditions. Gielen et al (), who exposed grassland populations to high temperatures over 3 years, did not observe improved PSII tolerance to midday stress compared with the control. In contrast, the midday depression of F V /F M was stronger for populations grown under high air temperature conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Our study on carbon fluxes on these same communities revealed that the adverse effects of warming were concentrated and likely confined to late spring and summer (De Boeck et al, 2007b). Apart from indirect effects of (summer) drought, direct negative effects of increased temperatures were also found, with summer fluorescence measurements indicating an increased intensity of midday stress as a result of heating, causing down-regulation of photosystem 2 (Gielen et al, 2007). Such direct temperature effects may have been of lower importance, as a study on the European heat wave in the summer of 2003 suggested that most of the adverse effects on productivity were caused by drought stress (Reichstein et al, 2007).…”
Section: Is Grassland Biomass Production Positively or Negatively Affmentioning
confidence: 84%
“…Importantly, the substantial knowledge gained through process-based studies in the same experimental platform, i.e. on autumn physiology (Gielen et al, 2005), water use (De Boeck et al, 2006a), photochemistry (Gielen et al, 2007) and CO 2 fluxes (De Boeck et al, 2007b) enables us to causally explain observed productivity responses.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect effects of warming through altered nutrient mineralisation and access to nutrients (Rustad et al 2001) are unlikely to have contributed either, as the plants were grown in sand with optimal nutrient supply. Direct effects of warming through enhanced (in native species) or alleviated (in alien species) temperature stress on plant growth are thus the most likely origin of the observed patterns (White et al 2000;Gielen et al 2007). Roots are particularly sensitive to temperature, and soil warming has been shown to reduce both root number and mass due to increased root death as a consequence of higher maintenance respiration (Atkin et al 2000;Edwards et al 2004;Wan et al 2004).…”
Section: Discussionmentioning
confidence: 95%